2010
DOI: 10.1016/j.otsr.2009.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Total Hip Replacement pseudotumoral osteolysis

Abstract: We report three cases of pseudotumoral lesion secondary to total hip replacement using metal on polyethylene bearings, presenting two distinct macroscopic aspects: (a) classic inflammatory granuloma and, in one case, (b) onset of hematoma associated with gluteal vessel lesions, probably affected by the pseudotumoral process. Diagnosis was radiographic, with CT-scan serving to confirm and, more importantly, to reveal extension and analyze surrounding tissue. Arteriography is needed when the lesion is liquid, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Hip plain radiography usually does not show signs of acetabular and femoral loosening. 5 , 9 , 11 , 15 Computed tomography of the pelvis, in turn, allows the identification of signs of pelvic osteolysis 14 and cystic mass adjacent to the implant. 2 , 6 , 11 , 14 In cases where the previous tests are normal, the MRI of the operated hip can be useful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hip plain radiography usually does not show signs of acetabular and femoral loosening. 5 , 9 , 11 , 15 Computed tomography of the pelvis, in turn, allows the identification of signs of pelvic osteolysis 14 and cystic mass adjacent to the implant. 2 , 6 , 11 , 14 In cases where the previous tests are normal, the MRI of the operated hip can be useful.…”
Section: Discussionmentioning
confidence: 99%
“…From the functional recovery point of view, assessed through questionnaires such as the Harris Hip Score and Merle D’Aubigne Postel scale, the surgical indication is beneficial. 9 , 14 Additionally, some pseudotumors may recur after drainage and more aggressive methods may be necessary, with no guarantee of good results. 16 Conversely, the refusal to accept a revision arthroplasty of the hip due to the presence of a pseudotumor should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Hjorth et al отмечают развитие осложнений в 19,5% случаев [8], тогда как S. Konan et al регистрируют 32% осложнений [9]. Локальные осложнения пары трения металл-металл проявляются в виде грануляционных разрастаний в ответ на металлические частицы [10][11][12]. Эти частицы (прежде всего, кобальта и хрома) образуются в результате износа пары трения, а также микроподвижности между головкой и конусом бедренного компонента эндопротеза.…”
Section: локальные осложненияunclassified
“…Osteolysis-related periprosthetic soft-tissue mass after total hip arthroplasty (THA) has been well documented [1][2][3][4][5][6][7][8]. Previous articles have reported that polyethylene particleeinduced osteolysis was caused by the existence of a periprosthetic soft-tissue mass and aseptic loosening of the implant [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%